2021
DOI: 10.1002/eat.23556
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐cognitive processing in people with eating disorders: Computerized tests of mentalizing, empathy and imitation skills

Abstract: Objective: Eating disorders are psychiatric illnesses characterized by extreme eating behaviors, such as sustained food restriction or loss of control over eating. Symptoms are thought to be maintained by a variety of mechanisms, one of which may be the socio-cognitive impairments associated with eating disorders. While some previous work has addressed socio-cognitive impairments in eating disorders, this work has relied mostly on self-report data.Method: Here we employed computerized tests of (a) mentalizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Despite differences in their clinical manifestations, people with eating disorders (EDs) often experience interpersonal problems and difficulties with social cognition that negatively affect their social functioning, quality of life, and daily activities [ 1 , 2 , 3 , 4 , 5 ]. Different psychological elements have been related to dysfunctional eating behaviors and interpersonal difficulties [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite differences in their clinical manifestations, people with eating disorders (EDs) often experience interpersonal problems and difficulties with social cognition that negatively affect their social functioning, quality of life, and daily activities [ 1 , 2 , 3 , 4 , 5 ]. Different psychological elements have been related to dysfunctional eating behaviors and interpersonal difficulties [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study found a tendency toward hypomentalizing among patients with ED (Cucchi et al, 2018), whereas another only found a tendency for hypermentalizing in this group (Cortés-García et al, 2020) and a third study found a tendency for both mentalizing impairments among ED patients (Corsi et al, 2021). Nevertheless, the results of a network…”
mentioning
confidence: 85%
“…However, clarity refers to the understanding of emotional experiences and the ability to differentiate between affective states, acceptance of emotions refers to the extent to which one accepts or rejects emotional experiences. Deranged emotion recognition has been detected in individuals with EDs (Oldershaw et al., 2011), but not through experimental methods (Corsi et al., 2021). Recently, the acceptance of emotions has been considered essential for adaptive emotion regulation: individuals who respond to their emotions with acceptance and a desire to understand and learn from them would generally be expected to functionally use their emotions to pursue valued actions (Gratz & Tull, 2022).…”
Section: Introductionmentioning
confidence: 99%